Three-dimensional Cu(OH)2 nanowire for highly efficient and selective uranium extraction from complex wastewater - Shaobin Cheng; Qingyan Zhang; Yifeng Hu; Binsheng He; Lei Shang; Xijun Fu; Yanlin Chen; Tao Cai; Qingyi Zeng (Desalination, 2026)

Self-propelled AzBA-algae microrobots enable rapid and stable dynamic remediation of sulfamethoxazole in aqueous environments - Jinxin Liu; Lin Cheng; Han Fu; Zhili Gao; Junjie Li; Jiawei He; Cheng Tian; Shusheng Zhang (Bioresource Technology, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Decadal gelatinization and phenological advancement of small jellyfish in Laizhou Bay, Bohai Sea - Ping Fu; Shan Sun; Huichao Jiang; Jianlong He; Ling Cheng; Bo Su; Hongyan Xing; Yuanqing Ma; Lijuan Liu; Yuting Zhao; Juan Zhang; Xiaowen Zhang (Marine Pollution Bulletin, 2026)

Middle Jurassic isolated dinosaur tracks from Msemrir (Central High Atlas, Morocco): Evidence for theropod occurrence and paleogeographic distribution - Noura Lkebir; Yao-Yan He; Xiong-Wei Zeng; Cheng-Gang Wang; Fa-Fu Wu; Lai-Shi Zhao; Zhi-Jun Niu (Palaeoworld, 2026)

Employment of magnetic measurements for monitoring conversion reactions in Fe3O4 anodes for lithium and sodium ion batteries - Bi Fu; Minghan Yang; Junfu Cheng; Zhanxu Chen; Yunbao Zheng; Yifang Li; Guangqi Hu; Yingji He; Chengzhi Hu; Yaping Wang (Chemical Engineering Journal, 2026)

Ecological and taxonomic significance of SEM‑based micromorphology in Gentiana (Gentianaceae) on the Qinghai‑Tibet Plateau - Ling Zheng; Yaqi Han; Xinyue He; Xiaoyu Zhou; Jingle Li; Peng-Cheng Fu (Flora, 2026)

Retraction notice to “Light absorption of black carbon and brown carbon in winter in North China Plain: comparisons between urban and rural sites” [Sci. Total Environ. 770 (2021) 144821] - Jiaxing Sun; Conghui Xie; Weiqi Xu; Chun Chen; Nan Ma; Wanyun Xu; Lu Lei; Zhijie Li; Yao He; Yanmei Qiu; Qingqing Wang; Xiaole Pan; et al. (Science of The Total Environment, 2026)

Novel eudesmanolides from the flowers of Pentanema britannicum (L.) D.Gut.Larr with antidepressant activities - Yu-Qing Xie; Xin-Yue Zhang; Jun-Hui Zhang; Ping He; Sheng-He Yang; Yan Fu; Zhi-Yu Ni; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

Microbiome immune crosstalk in Sjögren’s syndrome: mechanistic insights and translational perspectives - Xiang-Yu Qi; Meng-Yuan Wang; Tian-Chi Wei; Fu-Biao Shao; Shu-Han Liu; Ding Han; Jing-Wen Cheng; Yun-He Zhao; Lei Shi; Jing Luo; Ting Cheng; Sheng-Xiao Zhang (Immunologic Research, 2026)

Transglutaminase-induced crosslinking of soy protein isolate in crowded environments: effects of dextran concentration and molecular weight - Kaiyun Luo; Siqi Fu; Yunhao Xing; Xiaohong He; Maolong Chen; Zhou Xu; Ye Jiao; Yunhui Cheng; Xufeng Wang (Food Chemistry, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Genesis of the Zhamuqin Pb−Zn−Ag polymetallic deposit in the middle-southern Great Xing’an Range, NE China: constraints from H−O−S−Pb isotope geochemistry and geochronology - Peng He; Man Li; Shuo Guo; Fei Teng; Xianyu Cheng; Qilong Fu (International Geology Review, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Dynamic cultivar-soil interactions drive accelerating genetic gains in a dryland wheat system - Yuan Li; Yong-He Zhu; He-Peng Lu; Neng Wang; Fu-Ying Cheng; Yan-Lei Du; Feng-Min Li (Field Crops Research, 2026)

The Impact of Digestate Nitrogen Application Rate and DOC/TN Ratio on Soil Nitrogen and its Leaching in Pepper Cultivation - Fang Liu; Jianbo Jiang; Li Yang; Tengbing He; Tianling Fu; Tao Zhang; Qingxia Zhao; Xiangying Li; Jianbo Cheng (Journal of Soil Science and Plant Nutrition, 2026)

Analysis of the morphological structure and metabolic characteristics of Moniezia in sheep - Qian Mu; Wan-Ling Yao; Bao-Shan Wang; Wen-Zhu Chai; Fu-Hua Liu; Zhen Huang; Yong-Cheng Meng; Jing Pan; Xi-Ping Fan; Wan-Hong He; Wang-Dong Zhang (Veterinary Parasitology, 2026)

Improving resilience monitoring in non-stationary systems via a robust data-chunking algorithm - Linhai Cheng; Qiang Tang; Nan Lu; Chi Xu; Babak M.S. Arani; Changjia Li; Yafeng Wang; Xiangyi Li; Phuping Sucharitakul; Shuai Wang; Jie Wei; Junran Li; et al. (Science Bulletin, 2026)

Large-scale gold incorporation in bulk pyrite mediated by arsenic - Zi-Yue Gao; Kun-Feng Qiu; Razvan Caracas; Bing-Cheng Luo; Xin Liu; Zheng-Yu Long; Deng-Yang He; Jia-Nan Fu; Mei-Jing Xu; Hao-Cheng Yu; Zheng-Jiang Ding; Jun Deng (Geochimica et Cosmochimica Acta, 2026)

Exploring deep learning for seasonal dust prediction - Shikang Du; Yu Fu; Siyu Chen; Jiaqi He; Shuaiwen Wu; Wenhan Li; Shanling Cheng; Nan Yin (Atmospheric Environment, 2026)

From haploid inducer to CMS donor: repurposing of CENH3 to create a CMS line in a single step in Brassica napus - Mengyu Lei; Muhammad Zeeshan Mola Bakhsh; Xiaoyu Zhang; Dongli He; Cheng Dai; Chaozhi Ma; Jingxin Tu; Jinxiong Shen; Jing Wen; Tingdong Fu; Bin Yi (Plant Cell Reports, 2026)

Evaluating the performance of coastal virtual stations from different combinations of altimetry missions - Fukai Peng; Zhong He; Xiaoli Deng; Ole Baltazar Andersen; Dapeng Mu; Yunzhong Shen; Yanguang Fu; Xiao Cheng (Advances in Space Research, 2026)

New sesquiterpenoids from the flowers of Pentanema britannicum with cytotoxicity activities - Jun-Hui Zhang; Ping He; Sheng-He Yang; Jia-Li Lang; Yan Fu; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

Multi-omics chemical and biochemical profiling reveals ellagic acid enhances insulin sensitivity via gut microbiota–tryptophan–indole signaling mechanism - Zhihao Liu; Fu Zhao; Qihao Li; Qixiang Shang; Daozheng Fang; Xinyue Li; Haimeng Li; Quanrun He; Dapeng Zhang; Juanjuan Cheng; Yong Zhu; Zhongxia Li; et al. (Food Chemistry, 2026)

Green upcycling of tigogenin from sisal waste: Chemoenzymatic cascade synthesis of progesterone derivatives as an alternative to traditional steroid production processes - Lu Song; Zhi-Kun Luo; Fu-Cheng He; Lan-Ya Huang; Liang-Bin Xiong; Yong-Jun Liu; Dong-Zhi Wei; Feng-Qing Wang (Chemical Engineering Journal, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Carbonate rock dissolution regulates soil microbial iron and nitrogen cycle to reduce cadmium accumulation in rice - Fengling Liu; Hu Wang; Xu Mao; Jianbo Cheng; Bing Wang; Chengwu Fan; Tengbing He; Tianling Fu (Applied Soil Ecology, 2026)

Selective elimination of aniline contaminants induced by semiquinone radicals during peracetic acid oxidation of dihydroxybenzenes - Renjie Pan; Zheng-Xiong Zheng; Huan He; Tian-Yang Zhang; Chao Zeng; Qi Fu; Zhen-Ning Luo; Chen-Yan Hu; Tong-Cheng Cao; Mohamed Gamal El-Din; Bin Xu (Water Research, 2026)

Phototransformation of benzodiazepines in water mediated by dissolved black carbon: Mechanisms and the structure-reactivity relationship - Zhi-Cheng Zhou; Bin Yang; He-Yun Fu; Xiao-Lei Qu; Pei-Zhe Sun; Yong Feng; Guang-Guo Ying (Water Research, 2026)

CsNAC73 promotes cold-induced theanine biosynthesis by activating CsAlaDC expression in albino Camellia sinensis cv. Baiye 1 - Dandan Li; Ying Sun; Xin He; Xin Cheng; Maoyin Fu; Xuchun Zhang; Qi Chen; Xiaochun Wan; Linlin Liu (Plant Science, 2026)

Advancing dam health monitoring with high-resolution Fiber-optic Distributed Acoustic Sensing - Feng Cheng; Jianbo Guan; Jianghai Xia; Xinmin Zhu; Jiemin Fu; Xuhui Yu; Lei Tan; Zuyuan He (Engineering Geology, 2026)

Anammox community characteristics and stable relationships centered on anammox bacteria - Yi-Cheng Wang; Hui-Min Fu; Hong-Yuan Liu; Han Wu; Zi-Han Zeng; Jian-Hong He; Meng-Jiao Gao; Peng Yan; Liang Zhang; You-Peng Chen (Chemical Engineering Journal, 2026)

Neurophysiological and multimodal sensory evaluation of baijiu and food pairing liking - Yu Fu; Cheng Wang; Guoliang He; Shaohui Fan; Deliang Wang; Gaochong Lv; Lucas P.J.J. Noldus; Ting Jiang; Jie Huangfu (Food Research International, 2025)

Correction: Impact of BSG/CD147 gene expression on diagnostic, prognostic and therapeutic strategies towards malignant cancers and possible susceptibility to SARS-CoV-2 - Jiewen Fu; Binghui Song; Jiaman Du; Shuguang Liu; Jiayue He; Ting Xiao; Baixu Zhou; Dabing Li; Xiaoyan Liu; Tao He; Jingliang Cheng; Junjiang Fu (Molecular Biology Reports, 2025)

Mitochondrial damage causes inflammation via cGAS-STING signaling in ketamine-induced cystitis - Jinji Chen; Shengsheng Liang; Cheng Li; Bowen Li; Mingdong He; Kezhen Li; Weijin Fu; Shenghua Li; Hua Mi (Inflammation Research, 2025)

Development of a Private Cloud Platform for Distributed Logging Big Data and Its Application to Geo-Engineering Evaluation of Geothermal Fields - Xi Cheng; Hai-cheng Fu; Jun He (Applied Geophysics, 2025)

ARR1/12-ETP1/2 model negatively regulates submergence-induced hypoxia response in A. thaliana - Meng Liu; Xuerui Li; Zeyu Cheng; Yuhang Wu; Wensen Fu; Yongqi Hu; Jin Yan; Songfeng He; Wenli Chang; Ruijia Zhang; Yingying Qian; Jianquan Liu; et al. (Journal of Plant Physiology, 2025)

RBCK1 enhances antiviral response through promoting K63-linked polyubiquitination of IRF7 in Carassius auratus var. Pengze - Quanling Zhang; Tingting Yu; Zhongwei Wang; Miaomiao Li; Jingen Xu; Xuefeng Liu; Cheng Qian; Zijia Yin; Gang He; Menglei Hu; Binchao Zhang; Jiwei Liu; et al. (Fish & Shellfish Immunology, 2025)

Superwetting aqueous electrolyte for highly stable zinc anodes - Yurou Wu; Huijian Wang; Meilan Xie; Kai Fu; Zhendong Li; Xingyuan Dai; Jiarui Zhang; Lihan Wang; Xiaoshu He; Yidan Luo; Sheng Ouyang; Wen He; et al. (Chemical Engineering Journal, 2025)

van der Waals heterojunction-based NO2 chemosensor via a synergistic halogen bond site - Wen Luo; Huan Liu; Zhen Zhu; Bo Wang; Wenxing Xu; Ximeng Luo; Chunhui Li; Yanyan Fu; Huizi Li; Huimin Cao; Wei Xu; Qingguo He; et al. (Chemical Engineering Journal, 2025)

The critical role of OsYTH10 in promoting early flowering of rice under long sunlight - Jun Yang; Zhihao Chen; Peng Wang; Mvuyeni Nyasulu; Qin Cheng; Xiaopeng He; Jie Xu; Junru Fu; Dahu Zhou; Linjuan Ouyang; Haohua He; Jianmin Bian (Theoretical and Applied Genetics, 2025)

Real-time uncertainty quantification for KLT-based displacement estimation - Kang Zhou; Ming-Gang Duan; Ji-Yang Fu; Yun-Cheng He; Zi-Tong Li; Hai-Ou Shi; Jing Song (Engineering Structures, 2025)

Synergistic effect of charge-transfer bridge and surface defects for highly efficient photothermal catalytic CO2 reduction over 2D/3D SrTiO3/Zn0.5Cd0.5S - Peigen Ding; Zhanfei Fu; Liuna Zhang; Hongbin He; Jiarui Yang; Qi He; Zesheng Li; Jiale Cheng; Tian Gao; Xiaoming Gao (Chemical Engineering Journal, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Eutrophication‐induced dinoflagellate succession contributes to marine carbon sequestration through refractory dissolved organic matter accumulation - Fu‐Tao Fang; Zhuo‐Yi Zhu; Yuan‐Bi Yi; Ding He; Hong‐Yan Bao; En‐Ren Zhang; Cheng‐Xu Zhou (Limnology and Oceanography, 2025)
The increasing eutrophication of coastal seas is causing a shift in the most important phytoplankton groups from diatoms to dinoflagellates, but its feedback to marine carbon cycling remains unclear. Here, we investigated the potential of the key coastal phytoplankton, the diatom Skeletonema costatum , and the dinoflagellate Prorocentrum donghaiense , for refractory dissolved organic carbon (DOC) accumulation over dark degradation incubations of 70 d. Our multi‐method approach showed that dinoflagellate detritus, rather than diatom detritus, significantly contributes to refractory DOC. This is evidenced by the fact that the detritus of dinoflagellates compared to that of diatoms (1) has a weaker transmittance in infrared spectrometry, indicating a lower content of labile organic substances (alcohol and amide groups); (2) has a higher release and/or transformation efficiency of particulate organic carbon to DOC (81% vs. 50%); (3) has a lower content of labile fraction, amino acid (8% vs. 17% carbon) and exhibits lower degradability of the DOC formed (23% vs. 30%); (4) has a lower content of labile compounds determined by Fourier transform ion cyclotron resonance mass spectrometry (maximum molecular lability boundary: 21% vs. 31%); and (5) has a higher proportion of refractory carboxylic‐rich alicyclic molecules (57% ± 0.5% vs. 51% ± 0.7%) over incubations. Our results emphasize that eutrophication‐triggered coastal dinoflagellate succession has a significant potential for positive feedback to carbon sequestration through the formation of refractory DOC.

Antibiotic resistance gene transfer characteristic and risk evaluation: The entire process from swine manure to biogas slurry and then to soil - Pengcheng Liang; Hu Wang; Quanxu Chen; Qu Luo; Jianbo Cheng; Guangliang Tian; Tengbing He; Wenhai Zhu; Tianling Fu (Journal of Environmental Chemical Engineering, 2025)

Adsorption characteristics of sulfate reducing bacteria Clostridium sp. on lignite surface - Huan He; Zi Yang Zhou; Di Zhan; Yong Zhang; Wen Cheng Xia; Bo Fu; Feng Juan Lan; Xiu Xiang Tao; Zai Xing Huang (Environmental Science and Pollution Research, 2025)

Identification and characterization of Colletotrichum camelliae, the causal agent of leaf spot of Polygonatum odoratum in China - Rui Zhang; Yiyi Feng; Chun Wu; Ke He; Shaming Fu; Cheng Li (Crop Protection, 2025)

Selective production of olefins from methanol over a heteroatomic SAPO-34 zeolite - Zhaodong Zhu; Mengtian Fan; Meng He; Bing An; Yinlin Chen; Shaojun Xu; Tianze Zhou; Alena M. Sheveleva; Meredydd Kippax-Jones; Lutong Shan; Yongqiang Cheng; Hamish Cavaye; et al. (Science Bulletin, 2025)

Cytochrome P450 CYP6EM1 confers resistance to thiamethoxam in the whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) via detoxification metabolism - Mingjiao Huang; Peipan Gong; Cheng Yin; Jing Yang; Shaonan Liu; Buli Fu; Xuegao Wei; Jinjin Liang; Hu Xue; Chao He; Tianhua Du; Chao Wang; et al. (Pesticide Biochemistry and Physiology, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Hot syngas cleanup for pilot two-stage fluidized bed steam-oxygen biomass gasification plant - Zhijie Fu; Nazanin Charchi Aghdam; Sahand Nekoeian; Jing He; Long Cheng; Shida Liu; Lei Zhang; Junnan Chao; Xiaoyang Wei; Ruixu Wang; Bhavya Nagda; Yumeng Zhang; et al. (Bioresource Technology, 2025)

Reproductive biology of Plukenetia corniculata Sm. (Euphorbiaceae), a traditional wild vegetable in Southeast Asia - Cheng Feng; Yue Zhu; Qimei Su; Xiang Zhou; Weiyue Chen; Yan-Bin Tao; Maosheng Chen; Huiying He; Bang-Zhen Pan; Zeng-Fu Xu; Qiantang Fu (Genetic Resources and Crop Evolution, 2025)

Autonomous net inspection and cleaning in sea-based fish farms: A review - Jiaying Fu; Da Liu; Yingchao He; Fang Cheng (Computers and Electronics in Agriculture, 2024)

Fabrication, characterization, and bioactivity of self-assembled carrier-free colloidal dispersions from Citrus × Limon ‘Rosso’ essential oil and tea polyphenols - Fangying Cheng; Mianhong Chen; Zhihao Duan; Ying Zou; Yunxia He; Fanke Zeng; Yuan Yuan; Tiaokun Fu; Hao Tu; Ruyi Li; Jihua Li; Wei Zhou (Food Chemistry, 2024)

Real-time tilapia fillet defect segmentation on edge device for robotic trimming - Yingchao He; Weidong Xu; Da Liu; Maozhen Qu; Jiaying Fu; Fang Cheng (Computers and Electronics in Agriculture, 2024)

Aflatoxin B1 as a complicit in intestinal damage caused by Eimeria ovinoidalis in lambs: Novel insights to reveal parasite-gut battle - Pan Chen; Wen-li Ding; Bo-wen Xu; Mujeeb Ur Rehman; Kai-li Liu; Yan-feng He; Sen-yang Li; Fu-chun Jian; Shu-cheng(淑成) Huang(黄) (Science of The Total Environment, 2024)

Interactions between microbial communities and polymers in hydraulic fracturing water cycle: A review - Cheng Zhong; Rong Chen; Yuhe He; Deyi Hou; Fu Chen (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Mechanically strong SiC aerogels with broadband electromagnetic wave absorption enabled by hollow skeleton and interface engineering - Mingyuan Yan; Yuelei Pan; Pan He; Lunlun Gong; Yangyang Fu; Heping Zhang; Xudong Cheng (Chemical Engineering Journal, 2024)

Detoxification and neurotransmitter clearance drive the recovery of Arma chinensis from β-cypermethrin-triggered knockdown - Zhen Wang; Wenjie He; Luyao Fu; Hongmei Cheng; Changjin Lin; Xiaolin Dong; Chenxi Liu (Journal of Hazardous Materials, 2024)

Identification of stripe rust resistance gene YrBDT in Chinese landrace wheat Baidatou using BSE-seq and BSR-seq - Jingchun Wu; Yukun Cheng; Weihao Hao; Bin Bai; Luping Fu; Yan Ren; Yuanfeng Hao; Fengju Wang; Ruiming Lin; Hongqi Si; Chuanxi Ma; Zhonghu He; et al. (Theoretical and Applied Genetics, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

SLC11A1 promotes kidney renal clear cell carcinoma (KIRC) progression by remodeling the tumor microenvironment - Ding Wu; Yulin Zhou; Xiuquan Shi; Xiaoming Yi; Zhengcheng Sheng; Li Fan; Jingping Ge; Wen Cheng; Wenquan Zhou; Haowei He; Dian Fu (Toxicology and Applied Pharmacology, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Characterization of organic vapors by a Vocus proton-transfer-reaction mass spectrometry at a mountain site in southeastern China - Yi Zhang; Weiqi Xu; Wei Zhou; Yan Li; Zijun Zhang; Aodong Du; Hongqin Qiao; Ye Kuang; Lanzhong Liu; Zhiqiang Zhang; Xiao He; Xueling Cheng; et al. (Science of The Total Environment, 2024)

Potential of combined reactor and static composting applications for the removal of heavy metals and antibiotic resistance genes from chicken manure - Qu Luo; Hu Wang; Xiaoqing Lu; Can Wang; Ruiying Chen; Jianbo Cheng; Tengbing He; Tianling Fu (Journal of Environmental Management, 2024)

Novel material to enhance the integrity of CCUS cement sheath: Exploration and application of calcium aluminate cement - Peng Gong; Huacai Fu; Dan He; Yuanpeng Wu; Kaiyuan Mei; Chunmei Zhang; Xin He; Tao Liu; Shangdong Li; Xiaowei Cheng (Gas Science and Engineering, 2024)

Formation of lithium-rich pegmatites via rapid crystallization and shearing – case study from the South Tibetan Detachment, Himalaya - Xiao-Chi Liu; Matthew J. Kohn; Jia-Min Wang; Shao-Xiong He; Ru-Cheng Wang; Fu-Yuan Wu (Earth and Planetary Science Letters, 2024)

A comparative study on the degradation of carbamazepine by UV laser/chlorine and UV laser/PS processes: Performance and mechanisms - Qi Fu; Xing-Xing Wang; Huan He; Tian-Yang Zhang; Jian Lu; Meng-Yuan Xu; Renjie Pan; Tong-Cheng Cao; Mohamed Gamal El-Din; Bin Xu (Chemical Engineering Journal, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Toxicity of decabromodiphenyl ethane on lettuce: Evaluation through growth, oxidative defense, microstructure, and metabolism - Zhihua Qiao; Xinlin Sun; Kailin Gong; Xiuping Zhan; Kailun Luo; Mengru Fu; Shanqi Zhou; Yanna Han; Yuyou He; Cheng Peng; Wei Zhang (Environmental Pollution, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Immune-microenvironment modulatory polyurethane-hyaluronic acid hybrid hydrogel scaffolds for diabetic wound treatment - Yuan Feng; Kecen Xiao; Jinlin Chen; Jingjing Lin; Yuanyuan He; Xueling He; Fuyi Cheng; Zhen Li; Jiehua Li; Feng Luo; Hong Tan; Qiang Fu (Carbohydrate Polymers, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Local provincialism of late Permian plant–arthropod associations in South Cathaysia: Evidence of arthropod-mediated damages in a Wuchiapingian assemblage of South China - Fu-Jun Ma; Die-Die Luo; Song Liu; Cheng-Wan Zhang; Qiu-Jun Wang; Bing-Xia Li; Chuan-Yuan Liu; Bai-Nian Sun; Xiao He (Journal of Asian Earth Sciences, 2023)

Automatic modal identification via eigensystem realization algorithm with improved stabilization diagram technique - Wen-Hai Feng; Chao-Yuan Wu; Ji-Yang Fu; Ching-Tai Ng; Yun-Cheng He (Engineering Structures, 2023)

Experiment study on reactive powder concrete beams using spirals reinforcement under torsion - Xia Cao; Yong-peng Quan; Yi-cheng Ren; Feng Fu; Qi-zhi Jin; Da-bo He; Yan Zheng (Engineering Structures, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Cytochrome P450 CYP6DB3 was involved in thiamethoxam and imidacloprid resistance in Bemisia tabaci Q (Hemiptera: Aleyrodidae) - Xuegao Wei; Jinyu Hu; Jing Yang; Cheng Yin; Tianhua Du; Mingjiao Huang; Buli Fu; Peipan Gong; Jinjin Liang; Shaonan Liu; Hu Xue; Chao He; et al. (Pesticide Biochemistry and Physiology, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Hypothermic neuroprotection by targeted cold autologous blood transfusion in a non-human primate stroke model - Jian Chen; Shuaili Xu; Hangil Lee; Longfei Wu; Xiaoduo He; Wenbo Zhao; Mo Zhang; Yanhui Ma; Yuchuan Ding; Yongjuan Fu; Chuanjie Wu; Ming Li; et al. (Science Bulletin, 2023)

Airflow Mitigation and Pollutant Purification in an Idealized Urban Street Canyon with Wind Driven Natural Ventilation: Cooperating and Opposing Effects of Roadside Tree Plantings and Non-uniform Building Heights - Yu-Fei Tang; Ya-Bing Wen; Hao Chen; Zhi-Cheng Tan; Yi-He Yao; Fu-Yun Zhao (Sustainable Cities and Society, 2023)

Circulating polyunsaturated fatty acids, fish oil supplementation, and risk of incident dementia: a prospective cohort study of 440,750 participants - Yu He; Shu-Yi Huang; Hui-Fu Wang; Wei Zhang; Yue-Ting Deng; Ya-Ru Zhang; Qiang Dong; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (GeroScience, 2023)

Constitutive model for Ya’an mudstone based on mesoscopic breakage mechanism - Yun-yong He; Cong Chen; Fu-ming Wang; Cheng-chao Guo; Bo Xiang; Di Yu; En-long Liu; Chun Ding (Journal of Mountain Science, 2023)

Evidence of aircraft activity impact on local air quality: A study in the context of uncommon airport operation - Hao Xu; Kai Xiao; Jun Pan; Qingyan Fu; Xiaodong Wei; Junrui Zhou; Yamei Yu; Xue Hu; Huarui Ren; Jinping Cheng; Shitao Peng; Ningning Hong; et al. (Journal of Environmental Sciences, 2023)

A universal strategy for large-scale and controlled fabrication of conductive mesoporous polymer monolayers - Facai Wei; Bowen Chen; Jianwei Fu; Qingguo He; Chengbin Jing; Jiangong Cheng; Miharu Eguchi; Jongbeom Na; Yusuke Yamauchi; Shaohua Liu (Chemical Engineering Journal, 2023)

Impact of BSG/CD147 gene expression on diagnostic, prognostic and therapeutic strategies towards malignant cancers and possible susceptibility to SARS-CoV-2 - Jiewen Fu; Binghui Song; Jiaman Du; Shuguang Liu; Jiayue He; Ting Xiao; Baixu Zhou; Dabing Li; Xiaoyan Liu; Tao He; Jingliang Cheng; Junjiang Fu (Molecular Biology Reports, 2023)

Cobalt single atom anchored on N-doped carbon nanoboxes as typical single-atom catalysts (SACs) for boosting the overall water splitting - Tong Li; Siyuan Ren; Cheng Zhang; Lingxia Qiao; Jiang Wu; Ping He; Jia Lin; Yongsheng Liu; Zaiguo Fu; Qunzhi Zhu; Weiguo Pan; Baofeng Wang; et al. (Chemical Engineering Journal, 2023)

Cognitive changes are associated with increased blood-brain barrier leakage in non-brain metastases lung cancer patients - Da-Fu Zhang; Zhen-Hui Li; Zhi-Ping Zhang; Yin-Fu He; Bin-Li Shang; Xiu-Feng Xu; Ying-Ying Ding; Yu-Qi Cheng (Brain Imaging and Behavior, 2023)
To explore the relationship between cognitive function and blood–brain barrier leakage in non-brain metastasis lung cancer and healthy controls. 75 lung cancers without brain metastasis and 29 healthy controls matched with age, sex, and education were evaluated by cognitive assessment, and the Patlak pharmacokinetic model was used to calculate the average leakage in each brain region according to the automated anatomical labeling atlas. After that, the relationships between cognitive and blood–brain barrier leakage were evaluated. Compared with healthy controls, the leakage of bilateral temporal gyrus and whole brain gyrus were higher in patients with lung cancers ( P < 0.05), mainly in patients with advanced lung cancer ( P < 0.05), but not in patients with early lung cancer ( P > 0.05). The cognitive impairment of advanced lung cancers was mainly reflected in the damage of visuospatial/executive, and delayed recall. The left temporal gyrus with increased blood–brain barrier leakage showed negative correlations with delayed recall (r = -0.201, P = 0.042). An increase in blood–brain barrier leakage was found in non-brain metastases advanced lung cancers that corresponded to decreased delayed recall. With progression in lung cancer staging, blood–brain barrier shows higher leakage and may lead to brain metastases and lower cognitive development.

Bioinspired SiC aerogels for super thermal insulation and adsorption with super-elasticity over 100,000 times compressions - Mingyuan Yan; Xudong Cheng; Long Shi; Yuelei Pan; Pan He; Zhongxin Zhang; Zhiyi Lun; Yangyang Fu; Heping Zhang (Chemical Engineering Journal, 2023)

Influence of thermal hydrolysis on sludge anaerobic digestion: Release of humic acid promotes electron transport of methanogen - Cheng Zhao; Hongbo Liu; He Liu; Xinmin Zhan; Xuedong Zhang; Bo Fu; Mingze Shi; Shuailing Lu; Fang Huang; Minhua Cui; Yajie Li (Chemical Engineering Journal, 2023)

Combined population transcriptomic and genomic analysis reveals cis-regulatory differentiation of non-coding RNAs in maize - Jiawen Lu; Sihan Zhen; Jie Zhang; Yuxin Xie; Cheng He; Xiaoli Wang; Zheyuan Wang; Song Zhang; Yongxiang Li; Yu Cui; Guoying Wang; Jianhua Wang; et al. (Theoretical and Applied Genetics, 2023)

Application of regional citrate anticoagulation in patients at high risk of bleeding during intermittent hemodialysis: a prospective multicenter randomized controlled trial - Xiaoyan Tang; Dezheng Chen; Ling Zhang; Ping Fu; Yanxia Chen; Zhou Xiao; Xiangcheng Xiao; Weisheng Peng; Li Cheng; Yanmin Zhang; Hongbo Li; Kehui Li; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Study on the Effectiveness and Mechanism of Mercapto-Modified Attapulgite for Remediation of Cadmium-Contaminated Paddy Soil - Guangxi He; Xiaping Zhu; Yan An; Yuying Chen; Cheng Fu; Ningfei Lei; Ying Zeng; Junya Li; Zepeng Wang; Ping Zhao (Water, Air, & Soil Pollution, 2022)

Cytokine storm and targeted therapy in hemophagocytic lymphohistiocytosis - Han-qi Zhang; Si-Wei Yang; Yi-Cheng Fu; Ming-Cong Chen; Cheng-Hao Yang; Ming-Hua Yang; Xiao-Dan Liu; Qing-Nan He; Hua Jiang; Ming-Yi Zhao (Immunologic Research, 2022)

Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Cui-Ci Sun; Wei-Zhong Yue; You-Shao Wang; Wei-Hong He; Yi-Guo Hong; Fu-Lin Sun; Hao Cheng; Mei-Lin Wu; Zhao-Yu Jiang; Fei Jiao; Yu-Tu Wang (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSP color concentrations (CSP concentration determined spectrophotometrically) were 73.7–685.3 μg BSA eq L –1 [μg Bovine serum albumin (BSA) equivalent liter –1 ] in August 2016 and 100.6–396.4 μg BSA eq L –1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (<5), and declined from the river to the middle estuary by 80% in the wet season and 55.6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a (Chl a ) concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a /CSP color showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen (PN) pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6 × 10 6 mol N d –1 . These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

A female carrier of a novel DMD mutation with slightly skewed X-chromosome inactivation shows a suspected case of Becker muscular dystrophy in a Chinese family - Jianfan Chen; Hui Zheng; Zhongju Wang; Jian Wang; Fei He; Cheng Zhang; Fu Xiong (Molecular Genetics and Genomics, 2021)

Structure of SARS-CoV-2 main protease in the apo state - Xuelan Zhou; Fanglin Zhong; Cheng Lin; Xiaohui Hu; Yan Zhang; Bing Xiong; Xiushan Yin; Jinheng Fu; Wei He; Jingjing Duan; Yang Fu; Huan Zhou; et al. (Science China Life Sciences, 2021)

The Effect of Atractylodes macrocephala Polysaccharides on Rabbit’s Host Defense Peptide (RSRAH) mRNA Expression - Guihua Fu; Yang Zhang; Yinglun Li; Xing He; Xiaofen Li; Peng Cheng; Hongwei Chen (International Journal of Peptide Research and Therapeutics, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Evaluating three satellite-based precipitation products of different spatial resolutions in Shanghai based on upscaling of rain gauge - Weiyue Li; Xiaogang He; Weiwei Sun; Marco Scaioni; Dongjing Yao; Jing Fu; Yu Chen; Bin Liu; Jun Gao; Xin Li; Guodong Cheng (International Journal of Remote Sensing, 2019)

Meteorological conditions during a severe, prolonged regional heavy air pollution episode in eastern China from December 2016 to January 2017 - Xueliang Deng; Weihua Cao; Yanfeng Huo; Guanying Yang; Caixia Yu; Dongyan He; Weitao Deng; Wei Fu; Heming Ding; Jing Zhai; Long Cheng; Xuhui Zhao (Theoretical and Applied Climatology, 2019)

Evaluation genotypes of cancer cell lines HCC1954 and SiHa by short tandem repeat (STR) analysis and DNA sequencing - Jiewen Fu; Jingliang Cheng; Xiaoyan Liu; Jun Li; Chunli Wei; Xiaoli Zheng; Tao He; Junjiang Fu (Molecular Biology Reports, 2018)

Anticancer effect of Polyphyllin Ι in colorectal cancer cells through ROS-dependent autophagy and G2/M arrest mechanisms - Si Yu; Lijiao Wang; Zhixing Cao; Daoyin Gong; Qianyi Liang; Hanting Chen; Huizhu Fu; Wenwen Wang; Xue Tang; Zihao Xie; Yang He; Cheng Peng; et al. (Natural Product Research, 2018)

An Optimized and Feasible Preparation Technique for the Industrial Production of Hydrogel Patches - Wei-Ze Li; Wen-Xia Han; Xu-Liang Hao; Ning Zhao; Xi-Feng Zhai; Li-Bin Yang; Shu-Miao He; Yu-Chuan Cheng; Han Zhang; Li-Na Fu; Yan Zhang; Ze Liang (AAPS PharmSciTech, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

Imperatorin inhibits the expression of alpha-hemolysin in Staphylococcus aureus strain BAA-1717 (USA300) - Ping Ouyang; Junjie Chen; Mao Sun; Zhongqiong Yin; Juchun Lin; Hualin Fu; Gang Shu; Changliang He; Cheng Lv; Xuming Deng; Kaiyu Wang; Yi Geng; et al. (Antonie van Leeuwenhoek, 2016)

Removal of Color Compounds from Sugarcane Juice by Modified Sugarcane Bagasse: Equilibrium and Kinetic Study - Bo-hua Chai; He-cheng Meng; Zhen-gang Zhao; Qiang Huang; Xiong Fu (Sugar Tech, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Risk assessment of the city water resources system based on Pansystems Observation-Control Model of Periphery - Qiang Fu; Fanli Gong; Qiuxiang Jiang; Tianxiao Li; Kun Cheng; He Dong; Xiaosong Ma (Natural Hazards, 2014)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Optimization of fermentation process for the production of intracellular polysaccharide from Paecilomyces cicadae and the immuno-stimulating activity of intracellular polysaccharide - Jun-Wen Cheng; Yan-Bin Wang; Liang He; Hua Qian; Li-Zhong Fu; Hai-Bo Li (World Journal of Microbiology and Biotechnology, 2012)

Association between ATM 5557G>A polymorphism and breast cancer risk: a meta-analysis - Chen Mao; Vincent C. H. Chung; Ben-Fu He; Rong-Cheng Luo; Jin-Ling Tang (Molecular Biology Reports, 2012)

Fas/FasL pathway-mediated alveolar macrophage apoptosis involved in human silicosis - San-qiao Yao; Liying Wang Rojanasakul; Zhi-yuan Chen; Ying-jun Xu; Yu-ping Bai; Gang Chen; Xi-ying Zhang; Chun-min Zhang; Yan-qin Yu; Fu-hai Shen; Ju-xiang Yuan; Jie Chen; et al. (Apoptosis, 2011)

Oxytocin is expressed by both intrinsic sensory and secretomotor neurons in the enteric nervous system of guinea pig - Qiang Yu; Ruihua Ji; Xiaofei Gao; Jiqiang Fu; Wei Guo; Xianmin Song; Xiaolin Zhao; Geoffrey Burnstock; Xueyin Shi; Cheng He; Zhenghua Xiang (Cell and Tissue Research, 2011)

SCAR Makers and Multiplex PCR-Based Rapid Molecular Typing of Lentinula edodes Strains - Xueqian Wu; Haibo Li; Weiwei Zhao; Lizhong Fu; Huazheng Peng; Liang He; Junwen Cheng; Hailong Wei; Qingqi Wu (Current Microbiology, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Expression of P2X6 receptors in the enteric nervous system of the rat gastrointestinal tract - Qiang Yu; Zhengqing Zhao; Jihu Sun; Wei Guo; Jiqiang Fu; Geoffrey Burnstock; Cheng He; Zhenghua Xiang (Histochemistry and Cell Biology, 2010)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

Removal of dibutyl phthalate by a staged, vertical-flow constructed wetland - Wen Yu Zhao; Zhen Bin Wu; Qiao Hong Zhou; Shui Ping Cheng; Gui Ping Fu; Feng He (Wetlands, 2004)

An analysis of the air parcel trajectories of long- range transport at shanghai - Shao Demin; Zhang Wei; Shen Aihua; Cheng Xueqing; Fu Zhemin; He Zhenzhen (Advances in Atmospheric Sciences, 1992)